Aurora-A Induces Chemoresistance Through Activation of the AKT/mTOR Pathway in Endometrial Cancer - Wu, Jun; Cheng, Ziyun; Xu, Xiaofeng; Fu, Jian; Wang, Kaiyue; Liu, Tao; Wu, Chan; Kong, Xiangyi; Yang, Qian; Yan, Guijun; Zhou, Huaijun (Frontiers in Oncology, 2019)
Endometrial cancer (EC) is the most common gynecological tumor all over the world, and advanced/metastatic EC remains a malignancy with poor survival outcome due to highly resistant to conventional chemotherapeutic treatment. Here, we report that Aurora-A, a serine-threonine kinase, plays a vital role in chemoresistance of EC. Aurora-A is overexpressed in EC tissues, compared with normal endometrium and Aurora-A expression is associated with decreased overall survival. Overexpression of Aurora-A in EC cell lines (Ishikawa and HEC-1B cells) promotes cell proliferation and induced paclitaxel- and cisplatin-resistance. Furthermore, Aurora-A activating AKT-mTOR pathway further induces chemoresistance in vitro, consistent with a positive correlation between Aurora-A and phosphorylated AKT/4E-BP1 expression in EC tissues. In summary, our study provides the strong evidence that Aurora-A controls the sensitivity of EC cell lines to chemotherapy via AKT/mTOR pathway, indicating that pharmacologic intervention of Aurora-A and AKT/mTOR in combination with chemotherapy may be considered for the targeted therapy against EC with overexpression of Aurora-A.